Proinflammatory extracellular vesicle-mediated signaling contributes to the induction of neuroinflammation in animal models of endotoxemia and peripheral surgical stress - Fricke, Fabia; Gebert, Johannes; Kopitz, Jürgen; Plaschke, Konstanze (Cellular and molecular neurobiology, 2021)
Peripheral inflammation induced by endotoxemia or surgical stress induces neuroinflammation thereby causing neurological symptoms ranging from sickness behavior to delirium. Thus, proinflammatory signaling must be operative between the periphery and the central nervous system (CNS). In the present study, we tested whether nanometer-sized extracellular vesicles (EVs) that were produced during the peripheral inflammatory process have the capacity to induce neuroinflammation. Conditions of endotoxemia or surgical intervention were simulated in rats by lipopolysaccharide (LPS) injection or partial hepatectomy (HpX). EVs were concentrated from these animals and tested for their proinflammatory action (I) in a microglial cell line and (II) by intracerebroventricular and (III) by intravenous injections into healthy rats. EVs from both conditions induced the secretion of cytokines from the glial cell line. Intracerebroventricular injection of the EVs caused the release of inflammatory cytokines to the cerebrospinal fluid indicating their pro-neuroinflammatory capacity. Finally, proinflammatory EVs were shown to pass the blood-brain barrier and induce neuroinflammation after their intravenous injection. Based on these data, we suggest that EV-associated proinflammatory signaling contributes to the induction of neuroinflammation in endotoxemia and peripheral surgical stress. Preliminary results suggest that peripheral cholinergic signals might be involved in the control of proinflammatory EV-mediated signaling from the periphery to the brain.